Medium/Heavy duty truck test (Thomson Delmar Learning, 2007)
This updated fourth edition has been completely updated to provide the most current ASE test preparation material for Medium/Heavy Duty Trucks available anywhere. Test T4: Brakes provides valuable preparation for Medium/Heavy Duty Truck technicians seeking certification in the Brakes ASE Medium/Heavy Duty Truck Technician Certification area. Readers are afforded scores of opportunities to ascertain their knowledge of critical concepts, through the extensive array of sample problems, ASE-style exams, and competency-specific test questions required for certification by ASE. Refresher materials, helpful test-taking strategies, and thorough explanations round out this comprehensive preparation package.